Depresión en mujeres embarazadas - Puchaicela Campos, Patricia Magaly (2023)
Depression during pregnancy can significantly affect the health of the mother and her unborn child if it is not diagnosed and treated in time due to the hormonal changes and environmental factors experienced at this stage. The present curricular integration Project has as general objective to determine the scientific evidence of depression in pregnant women in Latin American countries, in a period from 2016 to 2022; A quantitative approach methodology was applied, with a longitudinal section and a documentary type based on bibliographic systematization. The study population was composed of scientific evidence published in the databases Redalyc, Dialnet, Google Scholar, Refseek, PubMed, BASE, SciELO, Medigraphic, DOAJ and ProQuest during the period 2016 to 2022, through the selection criteria the sample was delimited to 15 scientific articles of which it was identified that most of the scientific evidence corresponds to the countries of Mexico and Colombia in 2017; in pregnant women from 20 to 29 years of age with 75.57%; of married marital status with 47.64%; with a prevalent schooling level of high school with 72.47%; and a socioeconomic level of medium level with 67%; finding the prevalence of depression in the year 2021 with 63.64%, in the country of Chile with 75%. The existence of scientific production on this mental illness is evident, becoming an important precedent that allows mental health professionals to implement primary and secondary care strategies for the development and maintenance of this pathology